THE APPLICATION OF STUDENT FACILITATOR AND EXPLAINING METHOD USING MULTIMEDIA IN IMPROVING NATURAL SCIENCE LEARNING FOR THE FOURTH GRADE OF SDN 2 WALUYOREJO IN THE ACADEMIC YEAR OF 2014/2015 - Sentosa, Satria Suja (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: The Application Of Student Facilitator and Explaining Method Using Multimedia in Improving  Natural Science Learning for The Fourth Grade of SDN 2 Waluyorejo in the Academic Year Of 2014/2015. The objectives of this research are: (1) to describe the steps in the application of Student Facilitator and Explaining method using multimedia; (2) to improve natural science learning about resource of energy and sound for the fourth grade in SDN 2 Waluyorejo. This research is a collaborative Class Action Research (CAR). The experiment was conducted in three cycles. Subjects were fourth grade students of SDN 2 Waluyorejo in the academic year of 2014/2015, totaling 17 students. The results show that: (1) the application of student facilitator and explaining the multimedia has been implemented in accordance with the steps, namely: (a) introduction, (b) the delivery of the material competence, (c) the establishment of the group, (d) the assignment, (e) delivery of results in front of the class, (f) drawing conclusion of learning, (g) evaluation and closing, (2) the application of the Student Facilitator and Explaining using multimedia in natural science learning can improve students' learning process for the fourth grade students of SDN 2 Waluyorejo. Keyword: student facilitator adn explaining, multimedia, Natural Science